Intercandidate Facebook Agenda-Building Effect of Webb County Judge Election Campaigns on the US-Mexico Border - Maria de los Angeles Flores (Norteamérica)
Maxwell McCombs proposed a hypothesis that required testing in the digital media. McCombs predicted that the correlation between new media agendas would need to be greatly opposing rather than greatly redundant, like those typically found in traditional media agendas. This study tested McCombs’ hypothesis and provides evidence that confirms it. The research examines the Facebook (fb) agenda-building effect between two Democratic candidates, Danny Valdez and Tano Tijerina, who ran for the Webb County judge seat during the 2014 Texas primary. The census sample included a total of 246 fb posts, 73 percent from Valdez and 27 percent from Tijerina. The fb agenda-building effect of election issues showed a slight positive correlation (rho = + 0.286) between the two Democratic candidates. Similar behavior was observed in the fb agenda-building effect of positive personal attributes, showing a slight positive correlation (rho = + 0.386). These results show that both fb agenda-building effects have a weak degree of interdependence, indicating that the Democratic candidates’ agendas were independent of each other.